Changes on Livelihood Pattern in Agriculture Labourers - Sah Kanu, Birendra Prasad (Academic Voices: A Multidisciplinary Journal, 2020)
The study revealed that livelihood changing pattern isn't a single fact; it's tied other more social fact like education, awareness, health and so on. It found that low education status is the causes of poor health and poor hygiene. Livelihood patterns of grandfathers, fathers and childrens were drastically changed as well as labour relation too. Now, they were involved in many diverse fields of wage labor like as repairing, technician work in a hospital, mobile repair, tent-generator service, rickshaw pulling, brick making, tractor driver, auto-electrick-erikshaw, electricity works etc. Among them most of youths involved in the labor market, which is reverse to their parents; they choose or join where they got highy This study result is a contrast with mentioned in literature review all those four scholars i.e. Luintel (2010), Bhandari (2013) and Mondal (2008) but slightly matched with Mishra (2015) argument which is diversification and multiple activities households' livelihood are more prosperous than single tie workers. Urbanisation and city construction opens more opportunities to them for job, education, awareness and dignity.